Efektivitas Kombinasi Ekstrak Daun Salam Dan Daun Mint Sebagai Obat Kumur Alami - Karlina, Lilis; Rahayu, S. Si., M. Si., Triastuti (2016)
Moutwash is a solution used to rinse the mouth to avoid bacteria. One of the materials used to make natural mounthwash is the bay leaf and mint leaf. Bay leaves contain essential oils, flavonoids and tannins that can act as an antibacterial, while the mint leaves contain menthol which can give a fresh taste in the mouth. The purpose of the study is to determine the effectiveness of leaves extractsthe addition of mint leaves as a natural mouthwash and to know the organoleptic quality of the natural mouthwash of the bay leaves and the addition of mint leaves. The research design used Completely Randomized Design (CDR) of one factor that kind of mouthwash (S), S1: distilled water, S2: 60% of bay leafconcentration extract and 50% mint leaf concentration extract, S3: 70% of bay leafconcentration extract and 60% mint leaf concentration extract. Bacteria data population were analized using the Man-Whitney Test. The result showed that S1, S2 and S3 don't show significant result. Most of mouthwash products arebrown, the distinctive aroma of little mint bay leaves, a little taste of sepet, rather clear and acceptance in dominant society is S2 because it is little teste of sepet. The conclusion of this study is S2 and S3 treatment iseffectiveless in inhibiting the growth ofin spittle bacteria.